Industrialización de la semilla del Molle (schinus molle) para la elaboración de pimienta blanca y rosada - Cajilema Lema, Katerin Lisseth (2019)
The researching project was carried out in city Latacunga in Cotopaxi province Eloy Alfaro Parish Barrio Salache Bajo in the Technical University of Cotopaxi in the laboratories of the Agroindustrial Engineering career. The objective was to industrialize the seed of (Schinus molle) using the process of dehydration and grinding to obtain the pepper, by applying variables such as the type of seeds and the dehydration temperatures used, the respective analyzes that were carried out in LABOLAB (Food, Water and Related Analysis Laboratory), the experimental design that was applied is a DBCA where factor A is the type of seed (with shell and without shell) and factor B are the dehydration temperatures (60 ° C 65) ° C and 70 ° C) which was carried out in a constant time of 4 hours. The quantitative variables analyzed were: moisture, ash and ethereal extract. The microbiological variables analyzed were: count of mesophilic aerobic molds and yeasts and Escherichia coli. According to the analyzes there were, two better treatments were obtained (t_4 and t_1) where t_4 seed without peel (white pepper) at 60 ° C obtained a humidity percentage of 8,65%, ash 3,1% and ethereal extract 4,22% which was found in a range established according to Inen Condiments Standard 2532 as its maximum moisture values 15%, maximum ash 3,5% and ether extract min 6% and t_1 seed shell (pink pepper) obtained a humidity percentage of 9,45%, 4.32% ash and ethereal extract 5,21%, which is in a range established by the FAO since its humidity ranges is maximum 14% maximum ash 7% and ethereal extract min 6% If the project will give a try,the some impacts such as, environmental impact which willprevent the indiscriminate felling of trees which provides the raw material required for its development, benefiting the environment, social and economic impact which have new opportunities to get ajob getting. Keywords: Schinus molle, Industrialization, dehydration, seed, pepper.